Kesiapan Guru dan Dampak Hasil Evaluasi Kurikulum Merdeka PAUD Menggunakan Model CIPP - Luluk Asmawati; Lamijan Hadi Susarno; Bachtiar Sjaiful Bachri (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to evaluate the implementation of the Kurikulum Merdeka for early childhood education using the CIPP model. The evaluative research method employed the stages of context analysis, input, process, and product, using a qualitative approach. The research subjects were 11 early childhood education teachers at TKIT Muadz bin Jabal, Cilegon City. Research findings: (1) context, the institution has conducted a needs analysis for the implementation of the Kurikulum Merdeka, parents were very supportive, the curriculum was relevant to the development and needs of children; (2) input, teachers had participated in training on the implementation of the Kurikulum Merdeka, teachers create their own teaching modules, learning media in accordance with the teaching modules, (3) process, children learn through exploration, differentiated learning, formative and summative assessments, (4) product, the Kurikulum Merdeka improves children's ability to adapt to changing times, critical thingking, creatively, collaboratively, and communicatively, parents were satisfied with the learning implemented, and early childhood education services had improved. The evaluation using the CIPP model of the early childhood Kurikulum Merdeka has been successfully implemented, resulting in improved service quality, enhanced teacher competence, increased parental support for children, and optimal potential for early childhood development.